INCLUSION IN PRACTICE: STUDENTS WITH DISABILITIES IN HIGHER EDUCATION - Wellichan, Danielle da Silva Pinheiro; Souza, Camila da Silva (Universidade Estadual Paulista, Faculdade de Ciências e Letras de Araraquara, 2017)
Including those who should not have been excluded, this is the way that society should follow, however, it is still possible to witness how far we are from an equal rights in several segments of humanity. In higher education, for example, the growing number of enrollments at university level shows how people with disabilities can go far, demystifying years of exclusion history. And for this inclusion to happen, it is necessary to turn our gaze to what was once the focus of basic education, rethinking the whole concept of accessibility, practices and coexistence, revising the space of Higher Education as a whole. Through the literature review, we sought to construct the referential of this work to propose new discussions and perspectives regarding inclusion in universities.